LESSON LEARNED DARI BEBERAPA NEGARA YANG SUKSES MEMANFAATKAN BONUS DEMOGRAFI - Febri Pramudya Wardani; Rahel Sintadevi Siahaan; Yanti Krismayanti; KP Suharyono S Hadiningrat (PT. Pustaka Cendekia Publisher, 2024)
Abstract Demographic bonus is a phenomenon that provides an opportunity for a country to increase economic productivity through a demographic structure where the productive age population is larger than the non-productive age population. This study aims to analyze and identify success factors from various countries that have successfully utilized the demographic bonus, particularly in the Asian region such as Japan, South Korea, Singapore, and Malaysia. Using the Focus Group Discussion (FGD) method with experts in demographics, economics, and public policy, this research examines the strategies and policies implemented by these countries in four main aspects: education, employment, health, and economy. The results show that successful utilization of the demographic bonus is determined by the right combination of policies in improving human resource quality, creating quality employment opportunities, and strengthening health systems, supported by macroeconomic stability and good governance. These findings provide valuable lessons for countries currently experiencing the demographic bonus phase in designing effective and sustainable policies. Keywords: demographic bonus, public policy, economic development, human resources, governance